1957
DOI: 10.1128/jb.73.6.778-783.1957
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF α,ε-DIAMINOPIMELIC ACID IN THE CELLULAR INTEGRITY OF ESCHERICHIA COLI

Abstract: a, e-Diaminopimelic acid was first isolated from acid hydrolyzates of Corynebacterium diphtheriae by Work (1951). Subsequent studies by Dewey and Work (1952) and by Davis (1952) have demonstrated that a, e-diaminopimelic acid (DAP) can be decarboxylated to lysine and that the path of lysine synthesis apparently involves DAP as an intermediate. Davis (1952) reported that a mutant strain of Escherichia coli (173-25), isolated by the penicillin method (Lederberg and Zinder, 1948; Davis, 1948), had an absolute req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1958
1958
1989
1989

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…It has been shown that the presence of lanthionine in the medium of Dpm auxotrophic mutans of E. coli permits growth and prevents lysis at suboptimal concentrations of Dpm (12,17). Under these conditions, however, the shape of the E. coli cells was not normal, and they tended to form spheroplasts (12).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the presence of lanthionine in the medium of Dpm auxotrophic mutans of E. coli permits growth and prevents lysis at suboptimal concentrations of Dpm (12,17). Under these conditions, however, the shape of the E. coli cells was not normal, and they tended to form spheroplasts (12).…”
Section: Discussionmentioning
confidence: 99%
“…Lysis of other organisms can be induced by either the lack of a cell wall essential nutrient or by the action of an inhibitor of wall synthesis. The lack of diaminopimelic acid for Escherichia coli (Rhuland, 1957;McQuillen, 1958;Meadow, Hoare, and Work, 1957) is an example of the former and penicillin action (Liebermeister and Kellenberger, 1956;Lederberg, 1956;Hahn and Ciak, 1957;Shockman et al, 1958) of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The presence in the M. lysodeikticus cell sheath of an autolytic enzyme system cannot be excluded (Mitchell and Moyle 1956b). In the present experiments, the bacteria are grossly deprived of nutrient and do not divide to form the osmotically fragile naked cells observed by Meadow, Hoare, and Work (1957) and Rhuland (1957) when Escherichia coli is deprived only of a single agent believed essential to the synthesis of cell wall material. The fact that aged M. lysodeikticus bacteria are almost all dumb-bell shaped could mean, on the other hand, that the processes involved in the conversion to protoplasts are intimately linked with those of cell wall production and division.…”
Section: Discussionmentioning
confidence: 64%